Problem and solution implementingregulations the law on government of Aceh, Indonesia - Sulaiman Sulaiman; M. Adli; Teuku Muttaqin (Proceedings of AICS - Social Sciences, 2013)
Memorandum of Understanding between the Government of Republic of Indonesia and the Free Aceh Movement (MoU Helsinki) as a concrete step in the Aceh conflict termination results a consensus to establish the Law on the Government of Aceh (the LoGA). The law is very important not only to regulate the various sectors of the implementation of special autonomy in Aceh, but also to help determine the future prospects of peace for Aceh within the Unitary Republic of Indonesia (NKRI). In the legislation referred, it is determined that to must finish product implementing regulations. Without these products, not all of the content of the Law on Government of Aceh could be run. This paper aimed at answering any problems that occur in the process of completing the regulations implementating of the Law on Government of Aceh.Keywords:Regulations, Implementing, The Law on Government of Aceh.